Diagnostic and Predictive Values of Ferroptosis-Related Genes in Child Sepsis - Li, Zhi; Zhang, Chi; Liu, Yiqi; Wang, Fang; Zhao, Baoling; Yang, Junmei; Zhao, Yongjing; Zhao, Hong; Wang, Guiqiang (Frontiers in Immunology, 2022)
Background: Early diagnosis of sepsis in children was essential to reduce mortality. This study aimed to explore the value of ferroptosis-related genes in children with sepsis. Methods: We screened the septic children microarray dataset from GEO database and analyzed the ferroptosis-related differentially expressed genes(DEGs). Functional analysis of ferroptosis-related DEGs was performed. The protein-protein interaction network was used to identify hub genes. We explored the immune landscape of sepsis and controls. The value of hub genes in diagnosing sepsis was tested in training(GSE26440) and validation set(GSE13904), and ELISA was used to verify the diagnostic value of them in children with sepsis in our hospital. Results:A total of 2103 DEGs in GSE26440 were obtained, of which ferroptosis-related DEGs were 34. Enrichment analysis showed significant enrichment in ferroptosis and hypoxia pathways(ie. HIF-1 pathway). The top three genes(HMOX1, MAPK14, TLR4) were selected as hub genes. Immunological analysis suggested that 10 cell type (ie. CD8/CD4 T cells) were lower in sepsis. Immune checkpoint related genes CD274(PD-L1), HAVCR2(TIM3) and SIGLEC15 were overexpressed in sepsis. The AUROC for the diagnosis of sepsis for HMOX1 and TLR4 ranged from 0.77 to 0.81, while the AUROC of MAPK14 reached 0.935 and 0.941 in training and validation set. Serum ELISA results of HMOX1 and TLR4 showed no significant difference in differentiating sepsis. The AUROC of MAPK14 was 0.877. When the diagnostic threshold was 74.852 ng/ml, the sensitivity and specificity were 0.906 and 0.719, respectively. Conclusion: Ferroptosis-related gene MAPK14 is of considerable value in the early diagnosis of sepsis in children.